Предмет: Алгебра,
автор: valyashchenko20
Помогите!!! Решите уравнение (1-6х)(1+6х) все делиться на 4= 2-(3х-1) в квадрате
Ответы
Автор ответа:
0
( ( 1 - 6х )( 1 + 6х )) / 4 = 2 - ( 3х - 1 )^2
1 - 36х^2 = 4( 2 - ( 9х^2 - 6х + 1 ))
1 - 36х^2 = 4( 2 - 9х^2 + 6х - 1 )
1 - 36х^2 = 4 - 36х^2 + 24х
1 = 4 + 24х
24х = - 3
Х = - 1/8
Х = - 0,125
1 - 36х^2 = 4( 2 - ( 9х^2 - 6х + 1 ))
1 - 36х^2 = 4( 2 - 9х^2 + 6х - 1 )
1 - 36х^2 = 4 - 36х^2 + 24х
1 = 4 + 24х
24х = - 3
Х = - 1/8
Х = - 0,125
Похожие вопросы
Предмет: Английский язык,
автор: bergerlick888
Предмет: Русский язык,
автор: Elmira2008
Предмет: Математика,
автор: tahirsultanov
Предмет: Математика,
автор: maxim821